2019
DOI: 10.1108/jhr-09-2018-0090
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Dual Approach Program to promote sexual abstinence in Thai early female adolescents and improve parent-daughter sexual communication

Abstract: Purpose The purpose of this paper is to examine the effectiveness of abstinence-based sexual education programs delivered in parallel to Thai parents and their early adolescent daughters to promote sexual abstinence and improve communication regarding sexual topics between them and their parents. Design/methodology/approach A quasi-experimental design included groups of parent/daughter dyads; Group 1 (controls) (n=40), Group 2 Adolescent Program (n=40) and Group 3 Adolescent Parent Program (APP) (n=42). Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…The study showed factors associated with higher knowledge of safe sex were living with people other than parents, studying family planning and belonging to a religion that accepted the use of birth control. While parents may be an important source of information on sexual and reproductive health at some stages of adolescence, living more independently may reflect other opportunities for gaining knowledge and experience in these matters [29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed factors associated with higher knowledge of safe sex were living with people other than parents, studying family planning and belonging to a religion that accepted the use of birth control. While parents may be an important source of information on sexual and reproductive health at some stages of adolescence, living more independently may reflect other opportunities for gaining knowledge and experience in these matters [29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents may not be able to discern accurate from inaccurate information or safe or unsafe practices [ 30 ]. Communication with parents and more highly educated mothers was positively associated with attitudes towards safe abortion and confirms the importance of parent-adolescent communication regarding sexuality, reproductive health and skills development [ 32 – 35 ]. The study also affirms adolescents with sexual experience tend to hold more positive attitudes towards abortion [ 11 , 16 , 30 ].…”
Section: Interpretationsmentioning
confidence: 72%
“…17 Researchers in Thailand discovered that pre-coital behaviors were much higher among teenagers living in Bangkok who experienced parental disapproval of sex, exposure to pornographic media, low sexual refusal self-efficacy, and had a boy/girlfriend. 21 In northern Thailand, it was found that male adolescents were more inclined than female adolescents to participate in pre-coital behaviors and that pre-coital behaviors were significantly predicted by age, sexual refusal self-efficacy, having boyfriends or girlfriends, strict parenting style, parental support for sex, and perceived peer norms. 9 According to our previous publication, 5 Muslim adolescents had sexual experiences, 9% of whom did not use a condom, 41.3% and 54% had sexual intercourse more than once.…”
Section: Pacific Rim Int J Nurs Res • January-march 2024mentioning
confidence: 99%